Implementation of the Aldrete score reduces recovery time after non-anesthesiologist-administered procedural sedation in gastrointestinal endoscopy - Roelandt, Philip; Haesaerts, Rico; Demedts, Ingrid; Bisschops, Raf (Endoscopy International Open, 2022)
Background and study aims Procedural sedation and analgesia (PSA) by trained non-anesthesiologist physicians and/or nurses is often performed during endoscopic procedures. Discharge from the recovery area after monitored observation is frequently based on fixed time parameters or subjective clinical assessment. In this study, the effect of implementation of the Aldrete score on recovery time after procedural sedation was analyzed in a real-life setting.Patients and methods A prospective observational study of patients undergoing procedural sedation and analgesia during gastroscopy, colonoscopy or endoscopic ultrasound was performed. All procedures were randomly included to represent a real-life situation with different endoscopists, recovery nurses, endoscopy systems and indications. After a first observation period, all endoscopy nurses were trained to implement the Aldrete score when discharging patients, followed by a second observation period.Results During the first observation period, the average time spent in the recovery area was 59 ± 22 minutes after procedural sedation. After implementation of the Aldrete score, the recovery time decreased significantly to 47 ± 25 minutes (P < 0.01) with identical doses of procedural sedation and analgesia. The decrease in time was between 19 % and 35 % for the different endoscopic procedures.Conclusions Implementation of the Aldrete score after procedural sedation and analgesia significantly reduces the time spent in the recovery area. The score can be used to safely implement a discharge policy that provides more efficient and standardized management for an endoscopy service.